2016
DOI: 10.1002/masy.201500132
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Characterization of Composites Curing by Microwave Irradiation

Abstract: The present study aimed to assess the curing of composites based on fiberglass and epoxy resin subjected to various microwave irradiation power level and time. The conditions studied were monitored in order to provide thermal images of different times during the irradiation, allowing the visualization of the temperature distribution over time on the test specimens . The heating profile tests resulted in samples that were later analyzed. Pores and voids content, density and thickness were also evaluated accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Polymer/PPO-GNR However, several studies have conducted on successful (without degradation) accelerated curing of epoxy resins by means of controlled microwave heating [29,30,33,66,[90][91][92][93][94][95][96][97][98]. As reported in [99] microwave heating offers distinctive advantage of having a controlled selective and volumetric heating at a reduced duration compared to thermal rapid heating which is a time and energy consuming process.…”
Section: Fibre Optic Sensingmentioning
confidence: 99%
See 3 more Smart Citations
“…Polymer/PPO-GNR However, several studies have conducted on successful (without degradation) accelerated curing of epoxy resins by means of controlled microwave heating [29,30,33,66,[90][91][92][93][94][95][96][97][98]. As reported in [99] microwave heating offers distinctive advantage of having a controlled selective and volumetric heating at a reduced duration compared to thermal rapid heating which is a time and energy consuming process.…”
Section: Fibre Optic Sensingmentioning
confidence: 99%
“…Microwave heating is in the form of radiation in which energy is dissipated volumetrically as a result of the interactions between the material(s) and microwaves at molecular scale [85]. Microwave dielectric heating has been employed in a variety of applications such as vulcanisation of rubber [121], heating of foods [122,123] and bonding of composites [30,86,90,98]. Epoxies may be cured by absorbing microwave energy from a high frequency field and converting it to heat energy via molecular vibrations/rotations in the presence of an alternating field ( Figure 6).…”
Section: Microwave Heating Based On Dielectric Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the use of microwave radiation as an analytical tool, a comparatively large volume of research has been undertaken to investigate the effects (and potential benefits) of using microwaves in a formulation capacity. For example, it has been shown that microwave radiation can affect the viscosity and gelatinisation of industrially utilised starch [8], be applied to synthesise novel maize protein-based functional materials [9], curing composites [10], enhancing rates of reaction [11] and considered for biodiesel production [12]. Possibly the most researched area of microwave-based formulation is regarding pharmaceutical applications where the limited physicochemical properties of compounds can be a significant barrier in the development of new medicines, thus requiring intervention, such as through alternative formulation methods including microwave heating, to enhance their properties.…”
Section: Introductionmentioning
confidence: 99%